Macromol. Rapid Commun. 15/2015. Issue 15 (August 2015) - Wang, Linge; Topham, Paul D.; Mykhaylyk, Oleksandr O.; Yu, Hao; Ryan, Anthony J.; Fairclough, J. Patrick A.; Bras, Wim
<x xml:space="preserve">Abstract</x> Back Cover: A novel approach for producing more uniform, intact beads by electrospinning a self‐assembled block copolymer (BCP) solution is demonstrated. This approach allows a relatively high polymer concentration to be used, yet with a low degree of entanglement between polymer chains due to microphase separation of the BCP in a selective solvent system. Further details can be found in the article by L. Wang, * P. D. Topham, O. O. Mykhaylyk, H. Yu, A. J. Ryan, J. P. A. Fairclough, and W. Bras on page 1437.